2023
DOI: 10.1007/s12144-023-04477-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of moral norms and anticipated guilt on COVID19 prevention behaviors

Abstract: Studies have shown that older adolescents have a low perceived personal risk of COVID-19, and yet their ability and willingness to engage in COVID-19 prevention behaviors is imperative for community health. Thus, health communication scholars need to consider alternative psycho-social predictors of prevention behaviors that will assist in protecting others in a pandemic. Based on Schwartz's Norms Activation Model (NAM;Schwartz, 1977), we examined the relationship between moral norms and COVID-19 prevention beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Further, in previous studies moral norms were shown to predict not only behavior, but also to have a direct explanation path to intention on COVID-19 prevention behaviors. Indeed, based on people`s intention to protect others, feelings of moral obligation provide an incentive for more efforts to avoid crowded places (Hagger et al, 2020;Turner et al, 2023). In this research, we ascertained whether moral norms can explain risk perception, behavior and intention to avoid crowded places.…”
Section: Moral Normsmentioning
confidence: 99%
“…Further, in previous studies moral norms were shown to predict not only behavior, but also to have a direct explanation path to intention on COVID-19 prevention behaviors. Indeed, based on people`s intention to protect others, feelings of moral obligation provide an incentive for more efforts to avoid crowded places (Hagger et al, 2020;Turner et al, 2023). In this research, we ascertained whether moral norms can explain risk perception, behavior and intention to avoid crowded places.…”
Section: Moral Normsmentioning
confidence: 99%